(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
English as second language in reading among adults contributes their numerous ideas and make a great effort to master reading in English. Henceforth, reading material plays a major role, in designing the curriculum of teaching material. This process of making the teaching material must include diagnosing the essential learning tools for adults, synthesizing the context of the teaching material, pre- determining the outcomes of their learning, having the ethical code for the material to have a effective learning. Teachers should invest a great effort in a large measure for the planning of these teaching materials. The major intention of this paper involves the planning of the teaching material, and how it can be developed effectively in a classroom.